2021
DOI: 10.3389/fonc.2021.640000
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Male Accessory Breast Cancer: A Comprehensive Systematic Review

Abstract: BackgroundAccessory breast cancer is extremely rare, especially in male patients, and only a few cases have been reported in the literature. To date, no specific guidelines regarding its diagnosis and treatment are available.ObjectivesThis study aimed to investigate the guidelines for the diagnosis and treatment of male accessory breast cancer by reviewing the available literature on this disease.MethodsThe Web of Science, Cochrane, PubMed, and CNKI databases were systematically searched (last search: 30 Novem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Recently, some scholars have also conducted a systematic analysis of the treatment of male breast cancer. They concluded that at present, male parabreast cancer is mainly treated by surgical resection, supplemented with chemotherapy, radiotherapy, endocrine therapy, and other comprehensive treatments (Pang et al, 2021). There is no report on the use of trastuzumab monotherapy in metastatic male accessory breast cancer and its effect until 2022.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some scholars have also conducted a systematic analysis of the treatment of male breast cancer. They concluded that at present, male parabreast cancer is mainly treated by surgical resection, supplemented with chemotherapy, radiotherapy, endocrine therapy, and other comprehensive treatments (Pang et al, 2021). There is no report on the use of trastuzumab monotherapy in metastatic male accessory breast cancer and its effect until 2022.…”
Section: Discussionmentioning
confidence: 99%
“…A United States study showed male triple-negative breast cancer accounted for 5.5% of the male breast cancer (6), while Pang reported the incidence rate of accessory breast cancer is 0.3-0.6% of all the breast cancer (7). Given that majority of male axillary accessory breast degenerate, there are few cases of male axillary accessory breast (8).…”
Section: Discussionmentioning
confidence: 99%
“…As the disease progresses, patients usually seek consultation with the complaint of pain, reddish or purplish skin and swelling. Pang et al summarised that most of the 16 patients identified with male accessory breast cancer globally were Asian, with invasive ductal carcinoma as the most common pathological diagnosis 4. The presenting case is an elderly man, with a main complaint of reddish rash and a painless mass in the left axillary region for 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…Accessory breasts present when the superfluous glands do not degenerate or degenerate incompletely. The development of malignant transformation is very rare in male accessory breasts, with 16 case reports summarised globally 4. No instances of bilateral synchronous accessory breast cancer in a male patient have been reported throughout the world.…”
Section: Introductionmentioning
confidence: 99%